PREPARATION AND ORGANOLEPTIC TEST OF PURPLE SWEET POTATO (Ipomoea batatas L.) FLOUR USING THE HEAT MOISTURE TREATMENT (HMT) - Azhani, Nazuhra; Taib, Eva Nauli; Zahara, Nurlia; Nurrizwani, Nurrizwani; Riski, Anisa Ayu (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2023)
Processing purple sweet potatoes into flour is one way so that sweet potatoes can be used for a longer time. Currently, there are still many students who don't know about sweet potato flour. Therefore, the researchers tried to make purple sweet potato flour and found out the comparison of proximate tests for flour using organoleptic tests. This research used the Heat Moisture Treatment method and used organoleptic tests on 15 respondents, namely taste, color, aroma, appearance and even texture. carried out from 18 to 24 October 2023. This research was conducted at the Tarbiyah Faculty, Building A UIN Ar-Raniry. The results obtained in this study showed that 60% liked sweet potato flour very much, 20% liked it and only 13% did not like it.